Large balloon dilation for the treatment of recurrent bile duct stones prevents short‐term recurrence in patients with previous endoscopic sphincterotomy. Issue 5 (June 2013) - Harada, Ryo; Maguchi, Hiroyuki; Takahashi, Kuniyuki; Katanuma, Akio; Osanai, Manabu; Yane, Kei; Hashigo, Syunpei; Kaneko, Maki; Katoh, Ryusuke; Katoh, Shin
Abstract Background/purpose Our previous study revealed the efficacy and safety of the large balloon dilation (LBD) technique. However, there is insufficient objective data about the recurrence rate. The aim of this study was to compare the recurrence rate of common bile duct (CBD) stones between patients treated with and without LBD. Methods Patients with recurrent CBD stones treated between April 2006 and August 2010, and who had a history of endoscopic sphincterotomy (ES), were enrolled. Patients were excluded if they had a CBD diameter of less than 10 mm or if the diameter of their largest CBD stone was <10 mm. Results A total of 62 consecutive patients were investigated. From April 2006 to November 2007, 32 patients were treated without LBD (non‐LBD group; historical control). From December 2007 to August 2010, 30 patients underwent LBD (LBD group). The median follow‐up times in the LBD and non‐LBD groups were 517 and 1034days (p < 0.001), respectively. Kaplan—Meier analysis revealed a significantly lower incidence of recurrent CBD stones in the LBD group than in the non‐LBD group (p = 0.048). Conclusions LBD reduces the short‐term recurrence of CBD stones in patients with previous ES.